2020
DOI: 10.3390/diagnostics10090637
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Role of WT1 Immunohistochemical Expression in Uterine Carcinoma: A Systematic Review and Meta-Analysis across All Endometrial Carcinoma Histotypes

Abstract: Background: The diagnostic role of Wilms’ tumor 1 (WT1) is well known in gynaeco-pathological setting, since it is considered a specific marker of serous histotype and adnexal origin. Moreover, its oncogenic role has been recently highlighted in many cancers and it has also been regarded as a promising target antigen for cancer immunotherapy. However, the relationship between its expression and prognostic role in uterine cancer remains unclear. We analyzed the diagnostic and prognostic role of WT1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…There are other morphologic factors that might have an independent prognostic value in EEC, such as a tumor budding, microcystic, elongated, and fragmented (MELF) pattern of invasion and WT1 immunohistochemical expression [ 29 , 30 , 31 ], although data in this regard are scarce. The prognostic significance of these factors, their reproducibility and their possible integration in the current risk stratification system need to be further investigated.…”
Section: Endometrioid Carcinoma (Eec)mentioning
confidence: 99%
“…There are other morphologic factors that might have an independent prognostic value in EEC, such as a tumor budding, microcystic, elongated, and fragmented (MELF) pattern of invasion and WT1 immunohistochemical expression [ 29 , 30 , 31 ], although data in this regard are scarce. The prognostic significance of these factors, their reproducibility and their possible integration in the current risk stratification system need to be further investigated.…”
Section: Endometrioid Carcinoma (Eec)mentioning
confidence: 99%
“…Similarly to the aforementioned reports, these authors reported worse overall, disease-specific and progression free survival across the entire cohort of endometrial cancer patients expressing WT-1. Additionally, when looking only at cases of USC, the authors observed a significant decline in OS with WT-1 expression ( Angelico et al, 2020 ). Although the results of current study do not replicate these findings, it is important to again note that the reports by Hedley et al and Dupont et al represent only 29 patients in total and therefore the results are difficult to generalize to the population as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear pleomorphism and mitotic activity are often not striking [ 2 , 3 ]. By immunohistochemistry, CC-EC is characterized by negativity for estrogen receptor (ER), progesterone receptor (PR) and WT1, and positivity for Napsin A, HNF1β (hepatocyte nuclear factor 1, less specific in the endometrium than in the ovary), and α-methylacyl-coenzyme-A racemase (AMACR, still not validated) [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%